Cyclic movement frequency is associated with muscle typology in athletes - Bex, T.; Baguet, A.; Achten, E.; Aerts, P.; De Clercq, D.; Derave, W. (Scandinavian Journal of Medicine & Science in Sports, 2017)
There is a continuing research interest in the muscle fiber type composition (MFTC) of athletes. Recently, muscle carnosine quantification by proton magnetic resonance spectroscopy (1H-MRS) was developed as a new non-invasive method to estimate MFTC. This cross-sectional study aims to better understand estimated MFTC in relation to (a) different disciplines within one sport; (b) cyclic sport exercise characteristics; (c) within-athlete variability; and (d) athlete level. A total of 111 elite athletes (74 runners, 7 triathletes, 11 swimmers, 14 cyclists and 5 kayakers) and 188 controls were recruited to measure muscle carnosine in gastrocnemius and deltoid muscle by 1H-MRS. Within sport disciplines, athletes were divided into subgroups (sprint-, intermediate-, and endurance-type). The controls were used as reference population to allow expression of the athletes` data as Z-scores. Within different sports, endurance-type athletes systematically showed the lowest Z-score compared to sprint-type athletes, with intermediate-type athletes always situated in between. Across the different sports disciplines, carnosine content showed the strongest significant correlation with cyclic movement frequency (R = 0.86, P = 0.001). Both within and between different cyclic sports, estimated MFTC was divergent between sprint- and endurance-type athletes. Cyclic movement frequency, rather than exercise duration came out as the most determining factor for the optimal estimated MFTC in elite athletes.